PERAN TEKNOLOGI PENDIDIKAN DALAM PEMBELAJARAN PAI KELAS VIII PADA MASA PANDEMI COVID-19 DI SMP NEGERI 1 CIOMAS - Ana Kassyifa; Fahmi Irfani; Sutisna Sutisna (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is that SMPN 1 Ciomas is one of the formal educational institutions that implements distance learning so that teaching and learning activities are carried out from home. The implementation of distance learning is carried out online using technology that is connected to the internet network. In its implementation, there are many obstacles that hinder distance learning. In this study, the author aims to determine the role of educational technology and the ability of teachers to apply PAI learning with educational technology during the Covid-19 pandemic. The research method used is a descriptive qualitative method. Using a case study approach, which is a method used to collect and analyze data in a particular case. The results of the study indicate that the role of educational technology during the pandemic at SMPN 1 Ciomas during distance learning using technology is as an online learning medium, facilitating online learning, teaching and learning activities become more flexible, and technology literate. In practice, teachers have high science and technology literacy skills, classroom management skills, communication and social skills. Keyword: Educational Technology, Teacher ability, Online